Whole-Genome Sequencing and Potassium-Solubilizing Mechanism of Bacillus aryabhattai SK1-7 - Chen, Yifan; Yang, Hui; Shen, Zizhu; Ye, Jianren (Frontiers in Microbiology, 2022)
To analyze the whole genome of Bacillus aryabhattai strain SK1-7 and explore its potassium solubilization characteristics and mechanism, thus providing a theoretical basis for analyzing the utilization and improvement of insoluble potassium resources in soil. Genome information for Bacillus aryabhattai SK1-7 was obtained by using Illumina NovaSeq second-generation sequencing and GridION Nanopore ONT third-generation sequencing technology. The contents of organic acids and polysaccharides in fermentation broth of Bacillus aryabhattai SK1-7 were determined by high-performance liquid chromatography and the anthrone sulfuric acid method, and the expression levels of the potassium solubilization-related genes ackA, epsB, gltA, mdh and ppc were compared by real-time fluorescence quantitative PCR under different potassium source culture conditions. The whole genome of the strain consisted of a complete chromosome sequence and four plasmid sequences. The sequence sizes of the chromosomes and plasmids P1, P2, P3 and P4 were 5188391 bp, 136204 bp, 124862 bp, 67200 bp and 12374 bp, respectively. The GC contents were 38.25%, 34.41%, 33.63%, 32.83% and 33.72%. Strain SK1-7 mainly secreted malic, formic, acetic and citric acids during potassium fermentation. The polysaccharide content produced with an insoluble potassium source was higher than that with a soluble potassium source. The expression levels of five potassium-dissolving-related genes with the insoluble potassium source were higher than those with the soluble potassium source.